Stress induced by the COVID-19 health situation in a cohort of 111 subjects present in the Bataclan concert hall during the November 2015 terrorist attacks in Paris - Lionel Gibert; Wissam El-Hage; Frédéric Dutheil; Bruno Falissard; Marion Trousselard (European Journal of Psychotraumatology, 2021)
Background: The management of the psychological consequences of the COVID-19 pandemic is all the more difficult when subjects suffer from a prior psychiatric illness. BV13 is a 54-month prospective longitudinal cohort study of 111 subjects who were present in the Bataclan concert hall during the November 2015 terrorist attack in Paris. Objectives: Our first objective was to investigate the association between stress related to the COVID-19 pandemic and PTSD symptoms, notably with respect to two positive risk factors: trait mindfulness and social support. The second was to explore how PTSD severity mediated the relationship between trait mindfulness and COVID-19-induced stress. Method: The primary endpoint was evaluated using the COVID-19 Peritraumatic Distress Index (CPDI). PTSD symptoms were evaluated using the PTSD Check List Scale (PCL-5) during the sanitary crisis and two years before. Social support was assessed with a Likert scale that measured perceived support from family, friends and the workplace. Trait mindfulness was measured with the 14-item Freiburg Mindfulness Inventory (FMI). Results: 54 months after the attack, a univariate analysis identified a significant positive correlation between COVID-19 stress (CPDI) and PCL-5 (r=0.77, p<0.01) scores, on the one hand, and significant negative correlations with FMI (r=–0.59, p<0.01), and social support (r=–0.28, p<0.01) scores, on the other hand. In the multivariate model, CPDI scores were closely associated with PCL-5 scores (p<0.01) after adjustment for FMI and social support scores. CPDI and FMI scores were significantly associated (p=0.05), but not CPDI and social support scores (p=0.89). The PTSD score was a strong mediator of the relationship between trait mindfulness (FMI) and COVID-19 stress (CPDI) scores. Conclusion: PTSD symptoms diminished the beneficial impact of trait mindfulness on stress related to COVID-19. Our finding highlights that subjects with previous experience of trauma need specific treatment for PTSD symptoms during the COVID-19 crisis.